Implications of Electronic Journals for Information Institutions - Chaudry, Abdus Sattar; Wang, Zhihong (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Features of current electronic journals systems have been reviewed and practices of handling e-journals on serials control work. While most of the delivery and access systems are similar in browsing and searching facilities, there are variations in pricing policies, archiving, licensing, and access control methods that create problems for information institutions.